2016
DOI: 10.1177/1403494816665775
|View full text |Cite
|
Sign up to set email alerts
|

Risky substance use among young adults in the nightlife arena: An underused setting for risk-reducing interventions?

Abstract: Aims: Alcohol and illicit substance use among young adults carries the risk of adverse consequences like violence, injuries, risky sexual behaviour and ultimately development of possible addiction. The nightlife arena is a risk-setting for excessive substance use and the aims of this study were to examine prevalence rates and identify high-risk subgroups in this context. Methods: Patrons (n = 1099, response rate 76%) entering or exiting 12 popular licensed premises in downtown Oslo, Norway, completed an anonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 25 publications
8
34
0
1
Order By: Relevance
“…Nevertheless, significantly more men than women had a BAC level ≥ 0.10%, similar to the previous study of visitors at a Swedish EDM event [33]. In contrast, neither the study in Norwegian clubs [34] nor the study in clubs in San Francisco found any effect of gender on BAC levels.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, significantly more men than women had a BAC level ≥ 0.10%, similar to the previous study of visitors at a Swedish EDM event [33]. In contrast, neither the study in Norwegian clubs [34] nor the study in clubs in San Francisco found any effect of gender on BAC levels.…”
Section: Discussionsupporting
confidence: 82%
“…Significantly more men than women had a BAC ≥0.10% [33]. Nevertheless, most studies have measured BAC levels in other nightlife settings, such as pub, bars and nightclubs and were conducted in several European and American cities [3437]. Two of these studies reported that between 88 and 94% had detectable BAC levels with an average of approximately 0.10% [34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, new factors of risky behaviors may be more pervasive, such as the use of newly emerging synthetic drugs (synthetic cathinone, synthetic cannabinoids, ecstasy, ketamine, or methamphetamine) [20,21], or virtual interactive activities (e.g., online sexting [22] or online sexual harassment [23]). These emerging issues may lead to risky behaviors, such as higher probability of unsafe sex, mental health conditions, and drug dependence [22,[24][25][26]. The emergence of these problems may lead to the change of sexual behavioral patterns, especially among youths and adolescents [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that illicit drug use is highly prevalent amongst nightclub and festival attendees (Hughes, Moxham-Hall, Ritter, Weatherburn, & MacCoun, 2017; Miller, Byrnes, Branner, Voas, & Johnson, 2013; Miller et al, 2015; Nordfjaern, Bretteville-Jensen, Edland-Gryt, & Gripenberg, 2016; Palamar, Barratt, Ferris, & Winstock, 2016; Palamar, Griffin-Tomas, & Ompad, 2015; Palamar, Salomone, Vincenti, & Cleland, 2016). A recent national survey of Australian dance festival-attending adults found that 78.1% of recent users reported using an illicit drug at their last-attended festival, and of users, 85.1% reported use of ecstasy (Hughes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%